2009
DOI: 10.1080/13576500802383709
|View full text |Cite
|
Sign up to set email alerts
|

Lateralised repetition priming for featurally and configurally manipulated familiar faces: Evidence for differentially lateralised processing mechanisms

Abstract: Although early research suggested that the right hemisphere was dominant for processing faces, more recent studies have provided evidence for both hemispheres being involved, at least to some extent. In this experiment we examined hemispheric specialisations by using a lateralised repetition-priming paradigm with selectively degraded faces. Configurally degraded prime faces produced negative priming when presented to the left visual field (right hemisphere) and positive priming (facilitation) when presented to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 31 publications
4
17
0
1
Order By: Relevance
“…Lateralized repetition priming in the amygdala has already been reported in the visual modality (Bourne, Vladeanu, & Hole, 2009). Our results show that a similar effect occurs in the auditory domain as well, and that it extends to the TVA.…”
Section: Discussionmentioning
confidence: 73%
“…Lateralized repetition priming in the amygdala has already been reported in the visual modality (Bourne, Vladeanu, & Hole, 2009). Our results show that a similar effect occurs in the auditory domain as well, and that it extends to the TVA.…”
Section: Discussionmentioning
confidence: 73%
“…For instance, Calvo et al (2012) suggested, based on a series of experiments with 'blended' expressions (whereby the mouth is smiling but the eyes present a different basic emotion), that featural information from the mouth is accessible earlier (< 170 ms after onset) than a configural representation in which the conflicting content is included. As feature-based processing has been suggested to be left lateralized (Bourne et al, 2009), it might account for right visual field biases regarding positive emotions (i.e. happiness, and perhaps surprise, both of which have large featural changes).…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that featural processing of faces is leftlateralized (Bourne, Vladeanu, & Hole, 2009). Inverted ECFT trials thus control for the lowlevel visual properties related to the presentation of face stimuli, while also ruling out the possibility that any differences in biases between expressions can be accounted for by the fact that these simply have different visual properties, such as the distinct featural change in the mouth that indicates happiness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking at a forest, one can view it holistically in its global meaning (a forest), or focus on specific trees and attend to their local features. Many studies with healthy and brain-damaged patients have demonstrated that these two complementing modes of perception are lateralized in the brain; the RH mediates the grasp of the overall picture, while the LH is associated with attention to the details [275, 276, 277, 278, 279, 280, 281, 282, 283, 284, 285]. For instance, patients with a unilateral brain damage were shown a series of stimuli (letters or geometrical shapes) consisting of elements which had different meanings than the global feature (see example in Fig.…”
Section: Abnormal Social Behaviorsmentioning
confidence: 99%